Investigation of E2 protein surface charge to facilitate drug delivery. - Ashminder Kaur. (2012)
The physical characterization of the nanoparticles and their surface can be used to assess binding interactions with cells in biological conditions. The surface properties of E2 protein, a self-assembled protein cage, have not been investigated thoroughly. This study investigates the effect of pH and ionic strength on the surface charge of E2 protein using zeta potential. E2 protein, a subunit of the pyruvate dehydrogenase multienzyme complex, was produced in Escherichia coli (BL21 (DE3)). E2 protein has been found to be a negatively charged protein. The isoelectric point of E2 is found to be around 3.5 after it was suspended in 50 mM sodium phosphate buffer between pH 3 to pH 10. The hydrodynamic diameter of E2 when suspended in the different pH level was found to be very stable except in the region between pH 3 and pH 4, where agglomeration was observed. The decrease in zeta potential of E2 protein in 0M NaCl solution was observed and concluded that the protein retains optimum colloidal stability in this solution.